Frühkomplikationsrate bei hüftgelenknahen Frakturen: Abhängigkeit von der Versorgung im Bereitschaftsdienst und von Nebenerkrankungen = Early complication rate of fractures close to the hip joint - Muhm, Markus Joachim; Weiß, Christel; Winkler, Hartmut (Der Unfallchirurg, 2013)
Background: Guidelines advocate early surgery for proximal femoral fractures so that operations are frequently performed in on-call duty times. Multimorbid patients also suffer more frequently from postoperative complications. Does on-call duty or night shift services correlate with higher postoperative complication rates and what influence do comorbidities have? Patients and methods: In 300 patients (> 65 years) postoperative surgical and non-surgical complications were documented and correlated with comorbidities, on-call duty and night shift service times. Results: Postoperative complications were observed in 10.7 % of surgical and 62 % of non-surgical cases. Surgery in on-call duty and night shift times did not increase the postoperative complication rate. Comorbidities, age and ASA classification correlated with postoperative complications which significantly prolonged hospital stay. Conclusion: Surgery of proximal femoral fractures in on-call duty and night shift times is justified because postoperative complications are not increased. Comorbidities and higher age correlated with postoperative complications. Postoperative complications should be avoided because they result in prolonged hospital stay.